Attitude of Public Elementary School Teachers Towards Children with Special Needs in Tangerang Regency - Apriani, Lusi; Sidq, Sistriadini Alamsyah; Utami, Yuni Tanjung (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Education is a basic right of Indonesian citizens, including children with special needs. The presence of children with special needs in regular schools, most schools in Indonesia have provided special education services for children with special needs. This study aims to find out the tendency of public elementary school teachers' attitudes towards children with special needs in Tangerang district. This research method uses quantitative with a correlational research design. The population in this study is 40 public elementary school teachers in Tangerang Regency. This research took place in a public elementary school in the Tangerang Regency area. Virgin collection is carried out using an attitude scale. The scale of attitudes used was tested for validity through expert judgment and statistical calculations by Spearman Rho. The results of the study showed that teachers' attitudes towards children with special needs had a moderate category, namely 20 teachers (50%) with the results of the correlation between teachers' attitudes and children with special needs had a close relationship with the value (-0.189). So it can be concluded that children with special needs have a relationship with the attitude of the teacher given to the child.